Hybrid Crank-Nicolson numerical method to solve Heat Diffusion problems - Omar Abdullah Ajeel; Awni M.Gaftan (Tikrit Journal of Pure Science, 2023)
In this paper, we derive the hybrid Crank-Nicolson method based on the implicit method and the usual Crank-Nicolson method, where we get more accurate results and faster access to results. We also used Maple to implement the hybrid method and the results were identical